Detection of Bartonella and Rickettsia in small mammals and their ectoparasites in México - Sánchez-Montes, Sokani; Cabrera-Garrido, Martín Yair; Ríos-Muñoz, César A.; Lira-Olguin, Ali Zeltzin; Acosta-Gutiérrez, Roxana; Mata-Galindo, Mario; Hernández-Vilchis, Kevin; Navarrete-Sotelo, D. Melissa; Colunga-Salas, Pablo; León-Paniagua, Livia; Becker, Ingeborg (THERYA, 2019)
Fleas and sucking lice are important vectors of multiple pathogens causing major epidemics worldwide. However these insects are vectors of a wide range of largely understudied and unattended pathogens, especially several species of bacteriaâ€™s of the genera Bartonella and Rickettsia. For this reason the aim of the present work was to identify the presence and diversity of Bartonella and Rickettsia species in endemic murine typhus foci in Hidalgo, México. A cross-sectional study was carried out to collect small mammals and their associated ectoparasites during October, 2014. Samples of liver and ear of hosts, and ectoparasites were fixed in absolute ethanol and examined to identify the presence of Bartonella and Rickettsia DNA by the amplification of specific fragments of the gltA and ompB genes using conventional PCR. The recovered sequences were compared with those deposited in GenBank, and phylogenetic analyzes were carried out to identify the position of the pathogens detected with respect to the valid species previously reported worldwide. A total of 47 fleas and 172 sucking lice, belonging to five families (Ceratophyllidae, Leptopsyllidae, Ctenophtalmidae, Hoplopleuridae, Polyplacidae) and related to six species were collected from 40 rodents of four species and one shrew. Only four hosts (two P. beatae, and two R. norvergicus) were positive to Bartonella elizabethae, Bartonella vinsonii and Rickettsia typhi. In the case of ectoparasites, 23 specimens of two flea species (Peromyscopsylla hesperomys and Plusaetis mathesoni) tested positive for B. vinsonii. No evidence of Bartonella or Rickettsia was detected in any lice. Our findings represent the first record of Bartonella elizabethae a confirmed zoonotic pathogen causing endocarditis in México and several new associations of Bartonella with Mexican flea species, which highlight the importance of the establishment of active entomological surveillance in wildlife.